OPTIMIZATION OF SELF-MANAGED RIVER DREDGING OPERATIONS FOR THE SOUTH JAKARTA AREA - CINITRA SYAFIQA, FAHMADHIA
Floods always occur in DKI Jakarta. Reducing the impact or problem of flooding can be done by dredging the river. The DKI Jakarta Provincial Government maintains self-managed water resource infrastructure (SDA) by implementing the “Grebek Lumpur Program”. The dredging operation for 5 rivers in the South Jakarta area requires 33 dump trucks with an actual equipment operational cost of Rp 32,856,623,349. Due to the limitations of dump trucks, which are 30-units, the purpose of this study is to produce an optimal distribution of dump trucks to minimize equipment operational costs. Optimization of dump truck distribution is done by using genetic algorithm method using MatLab software with two simulations. The first simulation was obtained by operating 30 dump trucks on 5 rivers, the operation could be completed with equipment operating costs of Rp 31,649,462,048, where equipment operating costs decreased by 3.67% or Rp 1,207,160,301. The drawback that can be experienced is that there is no spare dump truck tool. The second simulation is obtained by operating 27 dump trucks on 5 rivers, the operation can be completed with equipment operating costs of Rp 29,619,803,432, where equipment operating costs decreased by 9.85% or Rp 3,326,819,917. The disadvantage that can be experienced is that if only 27-unit dump trucks are operated, the completion of the dredging operation is not according to plan.